Interference of state authorities in the internal affairs of religious organisations in 1917–1928 (on the example of Orthodoxy and Protestantism) - Yanushevich, Ivan I. (Journal of the Belarusian State University. History, 2021)
Using the example of the Orthodox and Protestant churches, the process of interference by state authorities in the internal affairs of religious organisations in 1917–1928 is considered. The mechanisms of influence on believers, clergy and the leadership of these structures are analysed. It is determined that the main pressure was exerted to obtain, including public, support for all decisions of state bodies concerning domestic and foreign policy. It is established that the authorities planned to reduce the number of parishioners of the canonical Russian Orthodox Church by granting preferences to other confessions and religious movements, as well as its fragmentation by inspiring schisms. An attempt to transfer the management of the Orthodox Church formed by state bodies in a group of clergy in a non-canonical way has been studied.
Keywords: Russian Orthodox Church; sectarian organisations; communist party; renovationism